The Implementation of The BSCS 5E Model Based on Multiple Representations in Ecosystem Materials on Problem Solving and Metacognitive Abilities - Purwaningsih, Sri Dyah Ayu; Mubarok, Ibnul (FMIPA UNNES, 2021)
This study analyses the students' problem solving and metacognitive abilities by applying the BSCS 5E model based on multiple representations to ecosystem material. This research is a pre-experiment using the One-Shot Case Study design. The research pupils were students of class X SMA N 1 Donorojo in the 2019/2020 academic year. The research sample was class X MIPA 2 and X MIPA 5, taken by purposive sampling. The methods used in data collection include tests, interviews and questionnaires. The results showed that the problem-solving ability was in the